Mechanical Model of Underground Shaft Coal Pocket and Deformation of Silo Wall in Coal Mines - Yongping Wu; Mingyin Liu; Wenyu Lv; Bosheng Hu (Advances in Civil Engineering)
In order to provide a theoretical basis for the design of underground shaft coal pocket and support parameters in coal mines, a mechanical model and a dynamic analysis of the silo wall are established based on the engineering background of Ganhe Coal Mine. The numerical calculation is carried out by using the new model. The back analysis of the silo wall damage in the actual project is carried out, and the deformation law and fracture mechanism of the silo wall affected by different lateral pressure coefficients are analyzed and studied research. Based on the Mohr–Coulomb strength criterion, five sets of orthogonal simulation experiments were carried out for lateral pressure coefficients of 0.6, 0.8, 1.0, 1.2, and 1.4, respectively. The results show that the lateral pressure coefficient is the main factor affecting the deformation of the silo wall, the radial displacement of the silo wall increases gradually with the increase of the lateral pressure coefficient, and the displacement follows the quadratic polynomial function distribution. The maximum tensile stress area of the silo wall is located in the middle and lower part of the shaft coal pocket, which better explains the engineering phenomenon that the actual fracture location of the silo wall is mostly concentrated in the middle and lower part of the underground shaft coal pocket. The targeted repair technology can be used for reference in engineering.